Effect of perioperative lidocaine infusion on the subjective quality of recovery after surgery: Protocol for an updated systematic review and meta-analysis - Qianli Huang; Changhui Shao; Wei Wei; Shan Ou (PLoS ONE, 2025)
Background Lidocaine is increasingly used for surgical patients requiring general anesthesia. However, its clinical benefits on postoperative recovery quality are not well established. Our main objective aims to summarize the evidence regarding the effectiveness of perioperative lidocaine infusion on postoperative subjective quality of recovery (QoR). Methods and analysis This protocol will be conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) guideline. This systematic review will include randomized controlled trials (RCTs) from their inception until December 31st, 2024 with no language restrictions. The major databases including PubMed, Embase, and the Cochrane library will be comprehensively searched and supplemented by a hand searching reference lists of all included articles. Searches will involve studies assessing the efficacy of the perioperative lidocaine infusion for improving postoperative QoR, in comparison to placebo, or on treatment. The two authors will independently screen studies, extract study data and assess bias risk of the studies. The subjective QoR (QoR-15, QoR-40) on postoperative day 1–3 will be defined as primary outcome, whereas secondary outcomes will include morphine consumption, incidence of postoperative nausea and vomiting, time to first bowel movement, time to first flatus, and length of hospital stay. A meta-analysis will be performed using Review Manager 5.3 software. Sensitivity analyses, subgroup analysis and publication bias will also be conducted. The evidence quality of pooled results will be assessed by the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. Discussion This review and meta-analysis is anticipated to provide the evidence for the role of intravenous lidocaine on the subjective quality of recovery after surgery. In addition, the findings from this review will help clinicians with developing effective and safe perioperative anesthetic management regimens for surgery patients. Study registration PROSPERO registration number: CRD42024585866